Bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite sodium ion battery negative electrode material and preparation method
By combining sulfur-nitrogen-co-doped carbon quantum dots with bismuth oxychloride and using mercaptoethanol as a bridge agent, the problems of low specific capacity and poor cycle stability in sodium ion batteries were solved, and high specific capacity and good cycle stability were achieved.
Patent Information
- Application Number
- CN202411610267.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-12
AI Technical Summary
When Bismuth oxychloride (BiOCl) is the negative electrode material of sodium ion battery, its specific capacity is low and its circulation stability is poor, which limits its development and application in the field of sodium ion battery.
By combining sulfur-nitrogen co-doped carbon quantum dots with bismuth oxychloride, the defects and doped atomic sites of sulfur-nitrogen co-doped carbon quantum dots are used as additional sodium storage sites, and strong binding between the two is achieved through mercaptoethanol as a bridge agent to form a stable binary complex.
The specific capacity and cycle stability of the negative electrode material of sodium ion battery are improved, and excellent electrochemical performance is achieved.
Smart Images

Figure CN119143176B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a negative electrode material for sodium ion batteries composited with bismuth oxychloride and sulfur and nitrogen co-doped carbon quantum dots and a preparation method thereof. Background Art
[0002] In recent years, researchers generally believe that the development of efficient electrochemical energy storage devices is one of the important means to alleviate the carbon-based energy crisis. Among them, sodium-ion batteries for large-scale energy storage are the current hot research direction. The negative electrode materials in sodium-ion batteries bear the role of sodiumization and de-sodiumization, which will significantly affect the battery performance. Therefore, exploring and developing new negative electrode materials that can efficiently store sodium ions has always been the research focus and hotspot in this field, and it is also an imminent practical issue.
[0003] Among many negative electrode materials, bismuth oxychloride (BiOCl) has the characteristics of wide raw material sources, low price, simple process, and green environmental protection. It is a typical two-dimensional layered material and is widely used in the field of energy catalysis. In addition, its interlayer structure is formed by van der Waals force connection, and there is also a built-in electric field from the bismuth oxide layer ((Bi2O2)2+) to the halogen ion layer ((X)-). The large interlayer spacing (0.737nm) of BiOCl can effectively receive the insertion and extraction of sodium ions, and the built-in electric field can promote the migration of electrons to its surface. It is a very potential negative electrode material for sodium ion batteries, and has therefore received widespread attention from scholars in the field. However, BiOCl has low electron migration rate and poor structural stability (nanoparticles are easy to agglomerate and three-dimensional structure is easy to collapse), which makes it have the following problems when used as negative electrode material for sodium ion batteries: 1. BiOCl has low specific capacity when used as negative electrode material for sodium ion batteries, resulting in poor rate performance; 2. BiOCl is easy to agglomerate and collapse when used as negative electrode material for sodium ion batteries, resulting in poor cycle stability. The above problems have seriously hindered the development and practical application of BiOCl in the field of sodium ion batteries. Summary of the invention
[0004] In order to solve the problems of low specific capacity and poor cycle stability when BiOCl is used as the negative electrode of sodium ion batteries, the present application provides a sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur and nitrogen co-doped carbon quantum dots and a preparation method.
[0005] The purpose of the present invention is achieved by the following technical solution: a method for preparing a sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, comprising the following steps:
[0006] Step 1: preparing bismuth oxychloride;
[0007] Step 2: Preparation of sulfur-nitrogen co-doped carbon quantum dots;
[0008] Step 3: Prepare a negative electrode material for a sodium ion battery by co-doping carbon quantum dots with sulfur and nitrogen and bismuth oxychloride in a mass ratio of 1:5 to 20.
[0009] Further, the preparation of bismuth oxychloride in step 1 specifically comprises the following steps:
[0010] Step 1.1: dissolving a bismuth source in a solvent to obtain a solution A;
[0011] Step 1.2: adding a template to solution A; wherein the molar ratio of the template to the bismuth source is 1:8-15;
[0012] Step 1.3: adding chloride to solution A in a molar ratio of Bi to Cl of 1:1 to 3 to obtain solution B;
[0013] Step 1.4: Stir solution B magnetically until it dissolves into a clear and transparent state;
[0014] Step 1.5: Transfer solution B to a hydrothermal reactor, heat to 120-160° C., keep warm for 12-15 hours, cool and filter to obtain a precipitate, wash and dry the precipitate to obtain bismuth oxychloride.
[0015] Furthermore, the bismuth source is bismuth nitrate pentahydrate or bismuth citrate; the solvent is ethanol, ethylene glycol or isopropanol; the template is hexadecyltrimethylammonium bromide; and the chloride is KCl or BiCl3.
[0016] Furthermore, in step 1.5, the heating rate is 10-15° C. / min.
[0017] Furthermore, the preparation of sulfur-nitrogen co-doped carbon quantum dots in step 2 specifically includes the following steps:
[0018] Step 2.1: dissolving an oxygen source in N,N-dimethylformamide to obtain solution C;
[0019] Step 2.2: Add the carbon source to solution C and stir magnetically until it is dissolved into a clear and transparent state to obtain solution D; wherein the mass ratio of the carbon source to the oxygen source is 2 to 4:1;
[0020] Step 2.3: Transfer solution D to a hydrothermal reactor, heat to 120-160°C, keep warm for 4-8 hours, and cool to obtain solution E;
[0021] Step 2.4: Adjust the pH value of solution E to 8-9;
[0022] Step 2.5: Centrifuge Solution E, take the precipitate and redissolve it in deionized water, centrifuge it again, and repeat 2 to 4 times;
[0023] Step 2.6: Put the precipitate into a dialysis bag, add deionized water for dialysis, and repeatedly change the deionized water until the deionized water becomes colorless and transparent;
[0024] Step 2.7: Take out the solution in the dialysis bag, evaporate it, and freeze-dry it to obtain sulfur-nitrogen co-doped carbon quantum dots.
[0025] Furthermore, the oxygen source is citric acid or sodium citrate; and the carbon source is thiourea.
[0026] Furthermore, in step 2.4, a KOH solution having a concentration of 0.1 to 0.2 mol / L is added to solution E to adjust the pH value of solution E.
[0027] Furthermore, the dialysis bag in step 2.6 is a dialysis bag with a molecular weight of 10,000.
[0028] Furthermore, the preparation of the negative electrode material for the sodium ion battery in step 3 specifically includes the following steps:
[0029] Step 3.1: dissolving sulfur-nitrogen co-doped carbon quantum dot solid powder in ethanol to obtain solution F;
[0030] Step 3.2: adding mercaptoethanol at a concentration of 12 to 16 mol / L to solution F, and refluxing under the protection of an inert atmosphere at 50 to 80° C. to obtain solution G; wherein the amount of mercaptoethanol added is 5 to 10% of the volume of ethanol;
[0031] Step 3.3: Add bismuth oxychloride to solution G, reflux under the protection of an inert atmosphere at 50 to 80° C., and after the reflux, continue to introduce an inert gas, and evaporate, filter, and dry to obtain a negative electrode material for a sodium ion battery.
[0032] The present invention also discloses a sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite, which is prepared by the above-mentioned method for preparing the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite.
[0033] Compared with the prior art, this application has the following beneficial effects:
[0034] (1) The present invention combines sulfur-nitrogen co-doped carbon quantum dots with bismuth oxychloride, and utilizes the abundant defects on the surface and edges of the sulfur-nitrogen co-doped carbon quantum dots and the doped S and N atomic sites as additional sodium storage sites, thereby improving the specific capacity of the negative electrode material of the sodium ion battery during charging and discharging.
[0035] (2) The present invention utilizes the steric hindrance effect and electrostatic repulsion effect of sulfur-nitrogen co-doped carbon quantum dots with carbon chains on the surface to inhibit the agglomeration and collapse of BiOCl materials, thereby improving the cycle stability of the negative electrode material for sodium ion batteries.
[0036] (3) In the present invention, mercaptoethanol is used as a bridging agent between sulfur-nitrogen co-doped carbon quantum dots and bismuth oxychloride. Its hydroxyl end (-OH) is connected to the sulfur-nitrogen co-doped carbon quantum dots, and its mercapto end (-SH) is connected to the bismuth oxychloride, thereby achieving a strong bond between the two components, forming a stable and reliable binary complex, and exhibiting excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The exemplary embodiments of the present application and their descriptions are used to explain the present application and do not constitute a limitation of the present application. In each figure, the same reference numeral represents the same component.
[0038] Figure 1 The present invention is a flow chart of the preparation method.
[0039] Figure 2 This is an XRD diagram of a sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared by the method of Example 1 of the present invention. DETAILED DESCRIPTION
[0040] Example 1
[0041] like Figure 1 As shown, a method for preparing a sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots specifically comprises the following steps:
[0042] Preparation of bismuth oxychloride, its specific steps are as follows:
[0043] Step 1.1: Dissolve 4.85 g of bismuth nitrate pentahydrate in 40 ml of ethylene glycol to obtain solution A.
[0044] Step 1.2: Add hexadecyltrimethylammonium bromide as a template to solution A; wherein the molar ratio of hexadecyltrimethylammonium bromide to bismuth nitrate pentahydrate is 1:10.
[0045] Step 1.3: Add KCL to solution A in a molar ratio of Bi to Cl of 1:1 to obtain solution B.
[0046] Step 1.4: Transfer solution B to a beaker and stir magnetically under atmospheric pressure until it dissolves into a clear and transparent state.
[0047] Step 1.5: Transfer solution B to a hydrothermal reactor with a polytetrafluoroethylene liner, with a filling degree of 80%; place the reactor in an oven, heat it to 160°C at a heating rate of 10°C / min, and keep it warm for 12 hours; after the insulation is completed, take out the reactor, cool it naturally to room temperature, take out the reactor liner, and filter it under pressure under 1000 mesh filter paper to obtain a milky white precipitate. Wash the precipitate alternately with deionized water and alcohol for 3 times. After washing, dry the precipitate in a 60°C vacuum drying oven for 12 hours, and grind it with an agate mortar and encapsulate it to obtain bismuth oxychloride.
[0048] The specific steps of preparing sulfur-nitrogen co-doped carbon quantum dots are as follows:
[0049] Step 2.1: Dissolve 2 g of citric acid in 20 ml of N,N-dimethylformamide to obtain solution C.
[0050] Step 2.2: Add 4 g of thiourea to solution C at a mass ratio of thiourea to citric acid of 2:1, and stir magnetically under atmospheric pressure until the solution is dissolved into a clear and transparent state to obtain solution D.
[0051] Step 2.3: Transfer solution D to a hydrothermal reactor with a polytetrafluoroethylene liner, filling it to 40%; place the reactor in an oven, heat it to 160°C at a heating rate of 10°C / min, and keep it warm for 6 hours; after the insulation is completed, take out the reactor, cool it naturally to room temperature, and transfer the reaction-completed solution in the liner to a clean beaker to obtain solution E.
[0052] Step 2.4: Add 0.1 mol / L KOH solution to solution E, stir magnetically for 30 min, and adjust the pH value of solution E to 8.5.
[0053] Step 2.5: Place solution E into a centrifuge tube, centrifuge at 10,000 r / min for 15 min, discard the supernatant, and retain the precipitate; redissolve the precipitate in deionized water, centrifuge again at 10,000 r / min for 15 min, and repeat 3 times.
[0054] Step 2.6: Take the precipitate and put it into a 10,000 molecular weight dialysis bag, add deionized water for dialysis, and repeatedly replace the deionized water until the deionized water becomes colorless and transparent.
[0055] Step 2.7: The solution in the dialysis bag was taken out, rotary evaporated to 2 mL, and freeze-dried at -50 °C for 48 h to form a solid powder to obtain sulfur-nitrogen co-doped carbon quantum dots.
[0056] The specific steps for preparing the negative electrode material of sodium ion battery are as follows:
[0057] Step 3.1: Weigh 100 mg of sulfur-nitrogen co-doped carbon quantum dots prepared by the above method and 1000 mg of bismuth oxychloride prepared by the above method at a mass ratio of 1:10. Dissolve the weighed sulfur-nitrogen co-doped carbon quantum dot solid powder in 100 ml of ethanol to obtain solution F.
[0058] Step 3.2: Solution F was placed in a three-necked flask, and 5% (i.e. 5 ml) of mercaptoethanol with a concentration of 14.3 mol / L was added to Solution F as a bridging agent. A reflux device was connected, and the mixture was refluxed at 70°C under nitrogen protection for 1 h to obtain Solution G.
[0059] Step 3.3: The weighed bismuth oxychloride was added to solution G, and refluxed at normal pressure for 2 hours under nitrogen protection at 70°C, and then nitrogen was continuously introduced to evaporate solution G to 20 ml, so that the bismuth oxychloride was connected to the O phase in the Bi-O layer. The evaporated product was filtered under pressure, and the obtained solid was placed in a vacuum drying oven at 60°C for drying. After drying, it was ground and sieved with a 3500 mesh standard sieve to obtain a bismuth oxychloride sodium ion battery negative electrode material loaded with 10% sulfur and nitrogen co-doped carbon quantum dots.
[0060] The sodium ion battery negative electrode material prepared by the above method, which is a composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, was tested in a constant current charge and discharge mode. The upper voltage limit was 4.8V and the lower voltage limit was 0V. The specific capacity was 482 mAh / g and the capacity retention rate was 62.2% after 200 cycles.
[0061] Example 2
[0062] The difference between this embodiment 2 and embodiment 1 is that in the step of preparing the negative electrode material of the sodium ion battery, 100 mg of sulfur-nitrogen co-doped carbon quantum dots and 500 mg of bismuth oxychloride are weighed at a mass ratio of 1:5, and the remaining steps are the same as those in the embodiment to prepare a bismuth oxychloride sodium ion battery negative electrode material loaded with 20% sulfur-nitrogen co-doped carbon quantum dots.
[0063] The sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared by the above method was tested, and the test conditions were the same as in Example 1. The specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this example was 451 mAh / g, and the capacity retention rate after 200 cycles was 57.5%.
[0064] Example 3
[0065] The difference between this embodiment 3 and embodiment 1 is that in the step of preparing the negative electrode material of the sodium ion battery, 100 mg of sulfur-nitrogen co-doped carbon quantum dots and 2000 mg of bismuth oxychloride are weighed at a mass ratio of 1:20, and the remaining steps are the same as those in the embodiment to prepare a bismuth oxychloride sodium ion battery negative electrode material loaded with 5% sulfur-nitrogen co-doped carbon quantum dots.
[0066] The sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared by the above method was tested, and the test conditions were the same as those in Example 1. The specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this embodiment was 221 mAh / g, and the capacity retention rate after 200 cycles was 35.2%.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that in the step of preparing bismuth oxychloride, hexadecyltrimethylammonium bromide is added to solution A as a template; wherein the molar ratio of hexadecyltrimethylammonium bromide to bismuth nitrate pentahydrate is 1:8.
[0069] Under the test conditions of Example 1, the specific capacity of the sodium ion battery negative electrode material prepared in this example and composed of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots is 407 mAh / g, and the capacity retention rate after 200 cycles is 51.3%.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that in the step of preparing bismuth oxychloride, KCL is replaced with BiCl3. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material prepared in this embodiment, which is a composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, is 315 mAh / g, and the capacity retention rate after 200 cycles is 38.2%.
[0072] Example 6
[0073] The difference between this embodiment and embodiment 1 is that in the step of preparing bismuth oxychloride, ethylene glycol is replaced by isopropanol. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this embodiment is 336 mAh / g, and the capacity retention rate after 200 cycles is 47.4%.
[0074] Example 7
[0075] The difference between this embodiment and embodiment 1 is that in the step of preparing sulfur-nitrogen co-doped carbon quantum dots, citric acid is replaced with sodium citrate. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this embodiment is 365 mAh / g, and the capacity retention rate after 200 cycles is 48.3%.
[0076] Example 8
[0077] The difference between this embodiment and embodiment 1 is that in the step of preparing sulfur-nitrogen co-doped carbon quantum dots, thiourea is added to solution C at a mass ratio of thiourea to citric acid of 4:1. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this embodiment is 389 mAh / g, the capacity retention rate after 200 cycles is 41.3%, and the cycle stability is 1.24 W / m.
[0078] Example 9
[0079] The difference between this embodiment and embodiment 1 is that in the step of preparing sulfur-nitrogen co-doped carbon quantum dots, the pH value of solution E is adjusted to 8. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material composited with bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared in this embodiment is 411 mAh / g, the capacity retention rate after 200 cycles is 52.7%, and the cycle stability is 1.34%.
[0080] Example 10
[0081] The difference between this embodiment and embodiment 1 is that in the step of preparing bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, the holding temperature is replaced with 120° C. Under the test conditions of embodiment 1, the specific capacity of the sodium ion battery negative electrode material prepared in this embodiment, which is a composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, is 421 mAh / g, and the capacity retention rate after 200 cycles is 56.8%.
[0082] Embodiment 11
[0083] The difference between Example 4 and Example 1 is that in the step of preparing bismuth oxychloride, bismuth nitrate pentahydrate is replaced by bismuth citrate, and the other steps are the same as those in Example 1.
[0084] The sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots prepared by the method of this embodiment was tested under the test conditions in Example 1. The specific capacity of the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots was 398 mAh / g, and the capacity retention rate after 200 cycles was 51.5%.
[0085] Comparative Example 1
[0086] In this comparative example, bismuth oxychloride was prepared according to the method in Example 1, and the prepared bismuth oxychloride was directly used as the negative electrode material of the sodium ion battery; that is, the negative electrode material of the sodium ion battery in this comparative example did not load sulfur-nitrogen co-doped carbon quantum dots. Under the test conditions of Example 1, the specific capacity of the negative electrode material of the sodium ion battery in this comparative example was 205 mAh / g, and the capacity retention rate after 200 cycles was 21.5%.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that in the step of preparing solution C, N,N-dimethylformamide is replaced by water; in the step of preparing solution D, thiourea is replaced by urea. That is, the carbon quantum dots prepared in this comparative example are not doped with S and N atomic sites. Under the test conditions of Example 1, the specific capacity of the sodium ion battery negative electrode material of this comparative example is 288mAh / g, and the capacity retention rate after 200 cycles is 55.3%.
[0089] Comparative Example 3
[0090] The difference between this comparative example and Example 1 is that in the step of preparing the negative electrode material of the sodium ion battery, 100 mg of sulfur-nitrogen co-doped carbon quantum dots and 1000 mg of bismuth oxychloride are weighed in a mass ratio of 1:10. The weighed sulfur-nitrogen co-doped carbon quantum dots and bismuth oxychloride are mixed and dispersed in ethanol, and after continuing to reflux at normal pressure for 2 hours under nitrogen protection at 70°C, nitrogen is continuously introduced and magnetically stirred to obtain a mixture; the mixture is evaporated and pressurized, and the resulting precipitate is placed in a 60°C vacuum drying oven for drying, and after drying, it is ground and sieved with a 3500 mesh standard sieve to obtain a bismuth oxychloride sodium ion battery negative electrode material of sulfur-nitrogen co-doped carbon quantum dots. That is, compared with Example 1, this comparative example does not add a mercaptoethanol bridging agent. Under the test conditions of Example 1, the specific capacity of the sodium ion battery negative electrode material of this comparative example is 431 mAh / g, and the capacity retention rate after 200 cycles is 11.2%.
[0091] The test results of the sodium ion battery negative electrode materials prepared by the methods in the above Examples 1-11 and Comparative Examples 1-3 show that: the sodium ion battery negative electrode material prepared by the method in Examples 1-11 combines sulfur-nitrogen co-doped carbon quantum dots with bismuth oxychloride, and utilizes the rich defects on the surface and edges of the sulfur-nitrogen co-doped carbon quantum dots and the doped S and N atomic sites as additional sodium storage sites, compared with the bismuth oxychloride sodium ion battery negative electrode material not loaded with sulfur-nitrogen co-doped carbon quantum dots in Comparative Example 1 or the sodium ion battery negative electrode material of bismuth oxychloride and carbon quantum dots composited without doping S and N atomic sites in Comparative Example 2, the sodium ion battery negative electrode material prepared by the method in Examples 1-11 greatly improves the specific capacity during charge and discharge.
[0092] In addition, it can be seen from Examples 1-3 that, at the beginning, the specific capacity of the negative electrode material of the sodium ion battery increases with the increase in the loading ratio of the sulfur-nitrogen co-doped carbon quantum dots, but after reaching a certain loading ratio, the higher the loading ratio of the sulfur-nitrogen co-doped carbon quantum dots, the lower the specific capacity of the negative electrode material of the sodium ion battery. This is because too high a loading amount of carbon quantum dots may cover the sodium storage sites of BiOCl itself, and because of the strong interface effect, the structure of BiOCl itself changes, thereby reducing its specific capacity and cycle stability. Therefore, the 10% sulfur-nitrogen co-doped carbon quantum dot loading ratio in Example 1 is the optimal ratio, and the specific capacity of the negative electrode material of the sodium ion battery during charging and discharging is the highest.
[0093] In addition, the sodium ion battery negative electrode material prepared by the method in Examples 1-11 utilizes the steric hindrance effect and electrostatic repulsion effect of sulfur-nitrogen co-doped carbon quantum dots with carbon chains on the surface to inhibit the agglomeration and collapse of the BiOCl material. At the same time, the method in Examples 1-11 uses mercaptoethanol as a bridging agent between sulfur-nitrogen co-doped carbon quantum dots and bismuth oxychloride. The hydroxyl end (-OH) of mercaptoethanol connects the sulfur-nitrogen co-doped carbon quantum dots, and its mercapto end (-SH) connects the bismuth oxychloride, achieving a strong bond between the two components to form a stable and reliable binary complex. Compared with the sodium ion battery negative electrode material in Comparative Example 3 to which no mercaptoethanol bridging agent is added, the sodium ion battery negative electrode material prepared by the method in Examples 1-11 improves the specific capacity during charge and discharge while also having good cycle stability. Among them, the sodium ion battery negative electrode material prepared by the method in Example 1 has the highest specific capacity during charge and discharge, and the best cycle stability performance. Its XRD diagram is as follows Figure 2 shown.
[0094] It can be seen from the test data in Comparative Example 3 that its capacity retention rate after 200 cycles is the lowest, that is, the cycle stability of the sodium ion battery negative electrode material prepared by the method in Comparative Example 3 is the lowest, even lower than the cycle stability when bismuth oxychloride is directly used as the negative electrode material of the sodium ion battery in Comparative Example 1. This is because the volume of the negative electrode material of the sodium ion battery prepared by the method in Comparative Example 3 changes during the charge and discharge process. Due to the absence of a bridging agent, the sulfur-nitrogen co-doped carbon quantum dots are separated and fall off due to unstable connection. The unconnected sulfur-nitrogen co-doped carbon quantum dots will become a factor that hinders the cycle, and therefore, the cyclability will be worse than that of pure BiOCl.
[0095] It should be noted that all features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive features and / or steps, can be combined in any manner.
[0096] In addition, the above specific embodiments are exemplary, and those skilled in the art can come up with various solutions inspired by the disclosure of the present invention, and these solutions also belong to the disclosure scope of the present invention and fall within the protection scope of the present invention. Those skilled in the art should understand that the present invention description and its drawings are illustrative and do not constitute a limitation of the claims. The protection scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, characterized in that: The following steps are involved: Step 1: preparing bismuth oxychloride; Step 2: Preparation of sulfur-nitrogen co-doped carbon quantum dots; Step 3: preparing a negative electrode material for a sodium ion battery according to a mass ratio of sulfur-nitrogen co-doped carbon quantum dots to bismuth oxychloride of 1:5 to 20; wherein, mercaptoethanol is used as a bridging agent to compound bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots to prepare a negative electrode material for a sodium ion battery.
2. The method for preparing a negative electrode material for a sodium ion battery of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots according to claim 1, characterized in that: The preparation of bismuth oxychloride in step 1 specifically comprises the following steps: Step 1.1: dissolving a bismuth source in a solvent to obtain a solution A; Step 1.2: adding a template to solution A; wherein the molar ratio of the template to the bismuth source is 1:8-15; Step 1.3: adding chloride to solution A in a molar ratio of Bi to Cl of 1:1 to 3 to obtain solution B; Step 1.4: Stir solution B magnetically until it dissolves into a clear and transparent state; Step 1.5: Transfer solution B to a hydrothermal reactor, heat to 120-160° C., keep warm for 12-15 hours, cool and filter to obtain a precipitate, wash and dry the precipitate to obtain bismuth oxychloride.
3. The method for preparing a negative electrode material for a sodium ion battery of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots according to claim 2, characterized in that: The bismuth source is bismuth nitrate pentahydrate or bismuth citrate; the solvent is ethanol, ethylene glycol or isopropanol; the template is hexadecyltrimethylammonium bromide; and the chloride is KCl or BiCl3.
4. The method for preparing a negative electrode material for a sodium ion battery of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots according to claim 2, characterized in that: The heating rate in step 1.5 is 10-15°C / min.
5. The method for preparing the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite according to claim 1, characterized in that: The preparation of sulfur-nitrogen co-doped carbon quantum dots in step 2 specifically includes the following steps: Step 2.1: dissolving an oxygen source in N,N-dimethylformamide to obtain solution C; Step 2.2: Add the carbon source to solution C and stir magnetically until it is dissolved into a clear and transparent state to obtain solution D; wherein the mass ratio of the carbon source to the oxygen source is 2 to 4:1; Step 2.3: Transfer solution D to a hydrothermal reactor, heat to 120-160°C, keep warm for 4-8 hours, and cool to obtain solution E; Step 2.4: Adjust the pH value of solution E to 8-9; Step 2.5: Centrifuge Solution E, take the precipitate and redissolve it in deionized water, centrifuge it again, and repeat 2 to 4 times; Step 2.6: Put the precipitate into a dialysis bag, add deionized water for dialysis, and repeatedly change the deionized water until the deionized water becomes colorless and transparent; Step 2.7: Take out the solution in the dialysis bag, evaporate it, and freeze-dry it to obtain sulfur-nitrogen co-doped carbon quantum dots.
6. The method for preparing the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite according to claim 5, characterized in that: The oxygen source is citric acid or sodium citrate; the carbon source is thiourea.
7. The method for preparing the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite according to claim 5, characterized in that: In step 2.4, a KOH solution having a concentration of 0.1 to 0.2 mol / L is added to solution E to adjust the pH value of solution E.
8. The method for preparing the sodium ion battery negative electrode material of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots composite according to claim 5, characterized in that: The dialysis bag in step 2.6 is a 10,000 molecular weight dialysis bag.
9. The method for preparing a negative electrode material for a sodium ion battery of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots according to claim 1, characterized in that: The preparation of the negative electrode material for the sodium ion battery in step 3 specifically includes the following steps: Step 3.1: dissolving sulfur-nitrogen co-doped carbon quantum dot solid powder in ethanol to obtain solution F; Step 3.2: adding mercaptoethanol at a concentration of 12 to 16 mol / L to solution F, and refluxing under the protection of an inert atmosphere at 50 to 80° C. to obtain solution G; wherein the amount of mercaptoethanol added is 5 to 10% of the volume of ethanol; Step 3.3: Add bismuth oxychloride to solution G, reflux under the protection of an inert atmosphere at 50 to 80° C., and after the reflux, continue to introduce an inert gas, and evaporate, filter, and dry to obtain a negative electrode material for a sodium ion battery.
10. A sodium ion battery negative electrode material composed of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots, characterized in that: The material is prepared by the method for preparing the sodium ion battery negative electrode material composite of bismuth oxychloride and sulfur-nitrogen co-doped carbon quantum dots as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Battery material
EP3930041A1
KR20240040987A